PENGARUH KEPEMIMPINAN KEPALA MADRASAH TERHADAP MOTIVASI KERJA GURU - Hanan Ka-Do; Bahaking Rama; St. Syamsudduha; Danial Rahman (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2023)
The purpose of this study was to analyze and examine the influence of the madrasah principal's leadership on the work motivation of teachers at the Ash-Sholihin Islamic Boarding School, Gowa Regency. This research is a quantitative research using ex post facto method. The population in this study were 107 people from 3 levels of education, namely Madrasah Ibtidaiyah, Madrasah Tsanawiyah, and Madrasah Aliyah at the Ash-Sholihin Islamic Boarding School. Determination of the sample is done through probability sampling by determining as much as 25% of the total population so that the resulting sample is 27 people. The instrument used was a questionnaire and the data obtained were then analyzed using descriptive statistics and inferential statistics through simple linear regression. The results of this study prove that the leadership of the madrasah principal has a positive and significant effect on teacher work motivation by 37.51% with the resulting regression equation is = 115.016 + 0.186X. These findings indicate that the better the leadership of the madrasah principal is applied, the higher the work motivation of teachers in carrying out their duties.